Entwickelt sich die Republik Korea monoregional? Eine Analyse der Bevölkerungsdichte und Bevölkerungsbewegungen 1965-1970 - Schwind, Martin (ERDKUNDE, 1977)
The natural regional division of South Korea favours the incremental value of the country, especially on the western and southern sides. The predominant agricultural population of the pre-war period increased in these parts of the country up to a level of 200 and more persons per km². In opposition to this there are less than 100 persons per km2 in the mountain ranges and on the East Coast. Industrialisation, which was vigorously promoted from 1962, helped to bring people back to less densely populated regions; Kyongsang Province, in particular, with centres at Taegu, Andong and the port of Pohang, underwent development. After 1966 retrogressive internal migration commenced. Young labour elements moved to Seoul and Pusan. Almost all the agricultural districts registered population losses. The structure of population distribution shows a tendency to regression to the pre-war situation. Thus Korea is once again divided into a densely populated West, including the South, and a more sparsely populated Centre and East. The structural position is similar to the contrast of Omote and Ura Japan. But whilst mono-regional development has been pursued in Japan for 70 years, even to the extent of being subsidised by the state, and has almost irreparably hardened, Korea is only entering upon such a development tendency. It ought to receive the attention of the State. Improvements to the infrastructure may help, but they can not alone arrest the tendency.